Low offer of housing for rent? : Tax incentives to reduce empty housing - Borgia Sorrosal, Sofía (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Spain has had an affordable housing problem for twenty years. In 2001 the National Institute of Statistics published a study announcing that the country had 3.1 million unoccupied houses. Ten years later, after the crisis in the real estate sector, another study showed the existence of more homes of up to 3.4 million empty homes. This work aims to carry out a review of the fiscal policies carried out both in Spain and in other countries so that empty homes go on the rental market.